2009
DOI: 10.1016/j.healthpol.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The population-level impacts of a national health insurance program and franchise midwife clinics on achievement of prenatal and delivery care standards in the Philippines

Abstract: Objectives Adequate prenatal and delivery care are vital components of successful maternal health care provision. Starting in 1998, two programs were widely expanded in the Philippines: a national health insurance program (PhilHealth); and a donor-funded franchise of midwife clinics (Well-Family Midwife Clinics). This paper examines population-level impacts of these interventions on achievement of minimum standards for prenatal and delivery care. Methods Data from two waves of the Demographic and Health Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
4
29
0
Order By: Relevance
“…Subgroup analyses in this moderate quality study showed that this health insurance program could reduce inequalities; with the strongest impacts among women in rural areas, those in the lowest wealth tertile and those who were employed [32]. …”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analyses in this moderate quality study showed that this health insurance program could reduce inequalities; with the strongest impacts among women in rural areas, those in the lowest wealth tertile and those who were employed [32]. …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were published in two years, 2003 [20,26-29] and 2009 [17,18,30,31], with five and four studies, respectively. One study was published in each of the following years: 1995 [32], 2004 [33], 2007 [34] and 2008 [35].…”
Section: Resultsmentioning
confidence: 99%
“…The PhilHealth has been reported to increase the uptake and standards of ANC. 27 Improvements in the quality of services in healthcare institutions through accreditation and the coverage of financial costs by insurance contributed to the increased use of ANC by Filipino women regardless of the sociodemographic status. 27 28 There was also an increase in the total number of midwives and rural (barangay) health units over the years, which addressed the problems of distance and lack of availability of health workers and ANC facilities.…”
Section: Discussionmentioning
confidence: 99%